Understanding energy-efficient heating appliance behavior change - Neves, Joana (2021)
Neves, J., & Oliveira, T. (2021). Understanding energy-efficient heating appliance behavior change: The moderating impact of the green self-identity. Energy, 225, 1-12. [120169]. https://doi.org/10.1016/j.energy.2021.120169